Water the epic struggle for wealth, power, and civilization - Solomon, Steven (Harper Perennial, 2011)
This book is an account of how water has shaped human society from the ancient past to the present. Far more than oil, the control of water wealth throughout history has been pivotal to the rise and fall of great powers, the achievements of civilization, the transformations of society's vital habitats, and the quality of ordinary daily lives. Today, freshwater scarcity is one of the twenty-first century's decisive, looming challenges, driving new political, economic, and environmental realities across the globe. In this book, the author offers a narrative portrait of the power struggles, personalities, and breakthroughs that have shaped humanity from antiquity's earliest civilizations through the steam-powered Industrial Revolution and America's century. It is an account of man's most critical resource in shaping human destinies, from ancient times to our dawning age of water scarcity.